Corrections officers' knowledge and perspectives of maternal and child health policies and programs for pregnant women in prison - Virginia Pendleton; Jennifer B. Saunders; Rebecca Shlafer (BMC, 2020)
Abstract Background In response to the dramatic increase in the number of women incarcerated in the United States-and a growing awareness that a small proportion of women enter prison pregnant and have unique health needs-some prisons have implemented policies and programs to support pregnant women (defined here as maternal and child health [MCH] policies and programs). Corrections officers (COs) are key stakeholders in the successful implementation of prison policies and programs. Yet, little empirical research has examined prison COs' knowledge and perspectives of MCH policies and programs, particularly the impact such policies and programs have on COs' primary job responsibility of maintaining safety and security. The objective of this mixed-methods study was to understand COs' knowledge and perspectives of MCH policies and programs in one state prison, with a specific emphasis on the prison's pregnancy and birth support (doula) program. Results Thirty-eight COs at a single large, Midwestern women's prison completed an online survey, and eight of these COs participated in an individual, in-person qualitative interview. Results indicated that COs' perspectives on MCH policies and programs were generally positive. Most COs strongly approved of the prison's doula program and the practice of not restraining pregnant women. COs reported that MCH policies and programs did not interfere, and in some cases helped, with their primary job task of maintaining safety and security. Conclusions Findings support expansion of MCH programs and policies in prisons, while underscoring the need to offer more CO training and to gather more CO input during program development and implementation. MCH services that provide support to pregnant women that are outside the scope of COs' roles may help reduce CO job demands, improve facility safety, and promote maternal and child health.